Transmissão vertical da infecção pelo HIV e da sífilis na faixa de fronteira terrestre do Brasil de 2010 a 2020 - Lannoy, Leonor Henriette de (2024)
Introduction: Mother-to-child (MTCT) of HIV and syphilis (congenital syphilis) are diseases that persist as public health issues in several parts of the world, and have been scarcely studied at the Brazilian land border strip (LBS). Measures to prevent MTCT of HIV and syphilis are widely known and Brazil has the necessary resources and technologies available. The Brazilian LBS is the 3rd largest land border in the world and, for the purposes of planning and promoting regional development, the National Regional Development Policy (PNDR) established the division of the region into three major arcs: North, Central and South. In turn, borders are unique spaces with potential and challenges that require differentiated programmatic public policies that take into account the specificity of each territory. Understanding the epidemiological situation of the problem in the region aims to contribute to the implementation of public policies and support the strategy of eliminating MTCT of HIV and congenital syphilis. Objectives: Understand MTCT of HIV and syphilis and analyze the provision of health services at the Brazilian LBS from 2010 to 2020. Methods: A quantitative, ecological, and cross-sectional evaluation study was conducted using secondary data from cases of HIV/AIDS, HIV in pregnant women, acquired syphilis (AS), syphilis in pregnant women (PS), and congenital syphilis (CS) registered in the Notifiable Diseases Information System (SINAN) between 2010 and 2020 and living in the Brazilian border municipalities. Information from the Live Birth Information System (SINASC), the Primary Care Health Information System (SISAB), the e-Gestor and the Medicines Logistic Control System (SICLOM Managerial) were also used. The variables studied included sociodemographic characteristics, prenatal and delivery data, as well as the availability of services and procedures. Detection rates of AS, PS, AIDS, HIV infection in children under 5 years old, HIV in pregnant women, and the incidence of CS were calculated. The MTCT rate of HIV was estimated based on the number of children infected with HIV per year of birth divided by the number of HIV-infected pregnant women reported by year of delivery. Trends in detection and incidence rates were calculated for the analyzed period. Thematic maps were constructed for spatial distribution analysis of detection rates and incidences using Quantum GIS (QGIS) version 2.18.6, and spatial analysis was evaluated local autocorrelation (local index of spatial association—LISA) by means of Local Moran’s I index, calculated using R software version x64 3.4.0. Results: In the LBS, among pregnant women diagnosed with syphilis, 23.7% were 15 to 19 years old, 34.2% were illiterate or had 14 only primary education, 7% were black, and 47% were of mixed race. Among pregnant women with HIV infection, 15.6% were 15 to 19 years old, 34.0% were illiterate or attended only primary education, 10.1% were black, and 42.1% were of mixed race. It was verified that in 2019 and 2020 approximately 90% of pregnant women in the LBS had four or more prenatal consultations. However, in the Northern arc, this proportion was only 82% in 2019 and 79% in 2020. Information on rapid testing (RT) for syphilis in the SISAB was available on 84% of the municipalities while RT performance for HIV was available on 92% of them. Sixty-eight percent of the municipalities recorded the administration of penicillin for syphilis treatment and 17% of them had Medication Dispensing Units. The time series analysis in the LBS showed a 48% average annual increase in PS case detection rates from 2010 to 2020, being 59.6% in the Northern arc, 28.8% in the Central arc, and 67.2% in the Southern arc. Regarding CS, there was an average increase of 38.4% in the LBS, being 18.3% in the Northern arc, and 65.7% in the Southern arc. The Central Arc showed no statistically significant upward trend in the incidence of CS. The annual variation rate in the detection of pregnant women with HIV infection in the LBS was 9.1%, with an increase of 19.6% in the Northern Arc, 11.4% in the Central Arc and 6.1% in the Southern Arc. On the other hand, the AIDS trend in children under 5 years old showed a reduction in the period analyzed; in the FFT it was -16.1%, in the Northern Arc -8.3%, in the Central Arc -19.2% and in the Southern Arc -17.7%. The spatial analysis by LISA showed that in 2019 there were clusters of high PS rates in municipalities of Acre, Mato Grosso do Sul, and Rio Grande do Sul. Clusters of CS and pregnant women living with HIV in Rio Grande do Sul, and transition areas (high-low) of AIDS in children under 5 in municipalities of Pará, Amazonas, Rondônia, and Mato Grosso do Sul, were also found. Conclusion: The study's findings reveal that MTCT of HIV and congenital syphilis persist as a major problem in Brazilian LBS and disproportionately affect women with low levels of schooling, adolescents and black women. However, its distribution is not homogeneous between the arcs, especially in the control of MTCT of HIV. There is a need to expand access to prenatal care and create mechanisms to guarantee the quality of care in general. To this end, public policies that contemplate inter-sectorial practices aimed at transforming specific social determinants of each arc and supporting binational mechanisms and agreements with legal instruments of integration are essential